The Effect of Mind Fullness Parenting (Mindting) Module on Father's Parenting Patterns - Dian Lestari; Rina Nursanti; Suprida Suprida (Indonesian Journal of Global Health Research, 2024)
Parental care greatly influences the growth and development of children. As a country with a strong patriarchal culture, the role of fathers in parenting is minimal. Mindfulness parenting is a pattern of parenting that consciously gives attention to children. The mindfulness parenting module (Mindting) has been previously developed and found suitable for use in this study. This study aims to assess the effect of this module on the parenting of fathers with children under five years old. This research method uses quasi-experimental with one group, pre-post test. The subjects of this study were fathers who have children under five years old totaling 35 results: There is an effect of the Mindting module with changes in father's parenting (p-value: 0.013). The Mindfulness Parenting (Mindting) module affects the father's parenting pattern significantly.